2021
DOI: 10.1111/jfpp.15454
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ethyl lauroyl arginate and lemon essential oil added edible chitosan film coating on biogenic amines formation during storage in mackerel fillets

Abstract: There are important limitations affecting product quality and human health during the production, processing, and consumption of seafood. Biogenic amines (BA), which are formed by microbial decarboxylation of amino acids in seafood, are important indicators of fillet quality due to their potential risks in food poisoning and bad odors (Yassoralipour et al., 2012). The importance of BAs for food is due to their potential toxicity when they are taken into the body more than the maximum intake specified in the Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In addition, edible films incorporated with LAE were also used for aquatic products preservation. Demircan and Özdestan Ocak (2021) found that edible chitosan film coating with LAE (0.1%, w/v) significantly inhibits bacterial growth and biogenic amines formation of mackerel fillets during storage at 2°C. Similarly, active starch-gelatin films with LAE could effectively inhibit the microbial growth in marinated salmon and extend the product shelf life in terms of microbial spoilage (Moreno et al, 2017).…”
Section: Aquatic Productsmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, edible films incorporated with LAE were also used for aquatic products preservation. Demircan and Özdestan Ocak (2021) found that edible chitosan film coating with LAE (0.1%, w/v) significantly inhibits bacterial growth and biogenic amines formation of mackerel fillets during storage at 2°C. Similarly, active starch-gelatin films with LAE could effectively inhibit the microbial growth in marinated salmon and extend the product shelf life in terms of microbial spoilage (Moreno et al, 2017).…”
Section: Aquatic Productsmentioning
confidence: 95%
“…Ethyl lauroyl arginate (LAE), also known as ethyl-N α -lauroyl-Larginate, is an amino acid-based cationic surfactant, which is synthesized from L-arginine, lauric acid, and ethanol. LAE is considered one of the most potent antimicrobial substances among novel food additives for its broad-spectrum antimicrobial activity against a wide range of bacteria, yeasts, and filamentous fungi (Ma et al, 2020;Demircan and Özdestan Ocak, 2021). The use of LAE as a food preservative has been approved by the Food Drug Administration (FDA), the European Food Safety Agency (EFSA), and other countries.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of spermidine, one of the highest baseline concentration levels was noted among all of the studied biogenic amines. This is due to it being a natural substance of living cells [37]. During storage, in the control, and at the same time, in the study groups, a slow increase, or in some cases, even decreases, were observed in the trend changes related to spermidine and spermine.…”
Section: Content Of Biogenic Amines In Fish Samplesmentioning
confidence: 75%
“…The samples covered with the innovative films contained significantly less of this amine compared to the controls. According to the CAS, fish and their products should not contain more than 100 mg/kg of histamine as a hygiene limit [37]. The limit for histamine was exceeded in the fish from the control group on the 10th day of storage (160.92 mg/kg), while for fish covered with innovative films, the level was significantly lower on that day (87.44 mg/kg), not exceeding the limits.…”
Section: Content Of Biogenic Amines In Fish Samplesmentioning
confidence: 99%
“…The surface colors ( L *, a *, b *) of each constituent fruit in the fruit salad were individually measured using a color measuring device (Konica Minolta CR‐400, Japan), following the procedure outlined by Demircan and Ozdestan ( 2021b ).…”
Section: Methodsmentioning
confidence: 99%